Analysis of growth resistance mechanisms and causes in tea plants (Camellia sinensis) in high-pH regions of Northern China - Li, Chun-Lei; Xu, Jing; Xu, Hong-Mei; Liu, Jie; Zhang, Long-Xiang; Wang, Zi-Kai (Frontiers in Nutrition, 2023)
Background In tea plantations with high-pH (pH > 6.5) in Northern China, tea plants are prone to yellowing disease, albinism, and reductions in components that contribute to plant quality, which affect the scale and rate of tea plantation development in Northern China. Methods To investigate the potential causes of these issues, Camellia sinensis cv. Pingyang Tezao and Camellia sinensis cv. Ruixue were planted in Shouguang city (a high-pH area, soil pH > 6.5) and Rizhao city (a normal-pH area, soil pH is 4.5–5.5), respectively; differences in growth morphology, pigment content, cell structure, quality-determining components, and element content of the two varieties in the two areas were analyzed. Results The results showed that tea leaves planted in Shouguang had varying degrees of yellowing disease and albinism; the pigment content in both varieties was significantly lower when planted in Shouguang compared with Rizhao. The cell structure was severely damaged and the main quality-determining components were decreased. Nitrogen (N), phosphorus (P), potassium (K), zinc (Zn), copper (Cu) and manganese (Mn) contents in the leaves of the two tea plant varieties were significantly lower when planted in Shouguang compared with those in Rizhao; the levels of these elements in Shouguang soil were significantly higher than in Rizhao soil. Calcium (Ca) contents in Shouguang soil was 9.90 times higher than that of Rizhao soil. Conclusions We conclude that the soil in high-pH areas hindered tea plant uptake of N, Zn, Cu, and Mn, which had a detrimental effect on chloroplasts and reductions in chlorophyll synthesis, contributing to yellowing disease and albinism. In addition, excessive calcium (Ca) in Shouguang soil was also an important contributor to these negative effects. High-pH soil hindered tea plant uptake of P and K, resulting in reductions in tea polyphenols, amino acids, and other major quality components.